Pertanggungjawaban Pidana Terhadap Pelaku yang Melakukan Perbuatan Menyuruh Anak sebagai Pengemis - Ni Nyoman Ayu Ratih Ganitri; I Nyoman Putu Budiartha; Luh Putu Suryani (Jurnal Preferensi Hukum, 2021)
Children are not only actively involved as beggars, but toddlers are also passively involved, where children under the age of two are carried in pathetic conditions to make other people feel sad and sorry, thus giving them money. This study aims to explain the qualifications of criminal acts of perpetrators who order children as beggars and examine criminal liability for perpetrators who commit acts of ordering children as beggars. This study used a normative legal research method with a problem and conceptual approach. Sources of data used were primary and secondary legal data. Data collection was done through a literature study by taking notes. The results of the study revealed that the act of begging is categorized as a violation of public order as regulated in Article 504 of the Criminal Code. Doing the act of ordering children as beggars can be classified as a crime and also as an act of violation. Everyone is prohibited from exploiting children in any form as regulated in Article 301 of the Criminal Code junto Article 76I and Article 88 of Law no. 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection.